Increasing play‐based commenting in children with autism spectrum disorder using a novel script‐frame procedure. Issue 2 (17th April 2015) - Groskreutz, Mark P.; Peters, Amy; Groskreutz, Nicole C.; Higbee, Thomas S.
<x xml:space="preserve">Abstract</x> Children with developmental disabilities may engage in less frequent and more repetitious language than peers with typical development. Scripts have been used to increase communication by teaching one or more specific statements and then fading the scripts. In the current study, preschoolers with developmental disabilities experienced a novel script‐frame protocol and learned to make play‐related comments about toys. After the script‐frame protocol, commenting occurred in the absence of scripts, with untrained play activities, and included untrained comments.